(untitled) (Neo Scientific Peer Reviewed Journal, 2023)
This article provides information on the formation, formation and development of terms related to money, accounting-based Financial Relations, Finance-Budget, Treasury sectors, which are among the economic spheres in Uzbek. The specificity of the terms of the economy acquired in the formation and development of the terminological system of economics is highlighted using examples of its formation and progress.